Fingerprinting the folding of a group I precursor RNA. - Emerick, V L (1994)
Evidence that folding of the Tetrahymena pre-rRNA follows a defined path and is rate-determining for splicing at physiological temperatures is presented. Structural isomers were separated by native polyacrylamide gel electrophoresis and their splicing activities were compared. GTP binding selectively shifts the active form of the pre-RNA to an electrophoretic band containing both spliced and unspliced RNA. In situ chemical modification provides evidence for base-pair rearrangements in the 5' exon and structural alterations in the intron core of partially and fully active forms. Transition to the fully active precursor requires high temperature, but the activation energy is lower than expected for opening of RNA helices. Implications for control of RNA conformation during splicing are discussed.